Saponins and Flavonoids from Adzuki Bean (Vigna angularis L.) Ameliorate High-Fat Diet-Induced Obesity in ICR Mice - Liu, Rui; Zheng, Yinan; Cai, Zongwei; Xu, Baojun (Frontiers in Pharmacology, 2017)
Background and purpose: As an herbal medicine, adzuki bean has been practiced since the Tang Dynasty of China to maintain health and control weight; this practice is still very popular in China nowadays. However, it is still lack of sufficient scientific basis to explain scientific principle of this popular civil practice in weight control using adzuki bean. The purpose of this study was to verify and explain the anti-obesity effects of adzuki bean through in vitro enzymatic assays, in vitro lipolysis and in vivo study of obese mice model. Methods: Inhibitory effects of flavonoids and saponins from adzuki bean (Vigna angularis) on pancreatic lipase, α-glucosidase activities, and noradrenaline -induced lipolysis were assessed. High fat diet induced obesity model was created to study anti-obesity effects of adzuki bean. Both serum and liver lipid parameters were determined after eight weeks intervention. Results: Adzuki bean extracts enhanced lipolysis. Compared to the final body weight of high-fat diet group, oral administration of adzuki bean significantly (p ＜ 0.05) reduced the final body weight of mice and adipose tissue accumulation. The adzuki bean intervention also significantly reduced the levels of serum triglyceride, total cholesterol, LDL-cholesterol, and liver lipid. Conclusion: Adzuki bean demonstrated the anti-obesity effects on mice, such effects may mediated through the inhibitory effects of flavonoids and saponins from adzuki bean on α-glucosidase and pancreatic lipase activities, and lipolysis enhancement effect of active components from adzuki bean.